Bending analysis of hybrid ferrocement hollow slabs - Rajkumar, D. Shoba; Sundararajan, R. (Journal of Structural Engineering, 2025)
The conventional reinforced concrete slabs can be replaced by ferrocement hollow slabs for the reason it requires a lighter supporting system. The hollow portion provided in the slabs restricts the passage of heat from outside and provide good thermal insulation¹. To study the moment curvature relationship, four Ferrocement slabs of length 3m and depth 140mm were cast with a width of 690mm at the top and 770mm at the bottom with cores along the length. The skeletal reinforcement of 8mm diameter TMT steel bars were provided in the top and bottom flanges. Three layers of hexagonal wire meshes with 0.5mm diameter wires were provided in the compression and tension flanges and also along the ribs in between the cores. Out of the four slabs two slabs were cast with polyester fibers of cut length 12mm mixed in the cement mortar matrix and the other two slabs were cast without fibers. The polyester fibers in the mortar matrix serve as secondary reinforcement bridging the cracks initiated due to loading and reduce their further propagation². The slabs were subjected to bending and their behavior under flexure was investigated. The moment curvature relationship was determined. A comparison between the experimental and analytical predictions is made in this paper.